Optimasi Proses Reduksi dan Flokulasi Cr(VI) oleh FeSO4 pada Limbah Simulasi Elektroplating - Mardiyanti, Riska; Basir, Djabal Nur; Musallam, Abdurrahman Noval; Mustawa, Muhammad Al (Pusat Studi Bahasa dan Publikasi Ilmiah, 2026)
The increasing activity of the electroplating industry contributes to environmental pollution through wastewater containing toxic and carcinogenic hexavalent chromium [Cr (VI)]. This study aimed to determine the optimum conditions for Cr (VI) reduction–flocculation using iron (II) sulfate (FeSO₄) and to evaluate its application in simulated multi-metal electroplating wastewater. Batch optimization was conducted by varying pH (3–11), contact time (1–60 minutes), FeSO₄ dosage (0.01–0.3 g), and initial Cr(VI) concentration (50–500 mg/L). Cr (VI) concentration was analyzed using UV–Vis spectrophotometry with 1,5-diphenylcarbazide reagent at a maximum wavelength of 541.5 nm. The optimum conditions were obtained at pH 8, 5 minutes of contact time, and 0.1 g of FeSO₄, achieving 99.89% removal of Cr (VI) from an initial concentration of 100 mg/L. In simulated multi-metal wastewater, the removal efficiency reached 99.9% with a final concentration of 0.0921 mg/L, meeting the applicable discharge standards. These findings provide practical implications as initial operational parameters and demonstrate the potential of FeSO₄ as a simple and rapid pre-treatment method prior to further treatment processes. Further studies are recommended to validate the method using actual electroplating wastewater and to evaluate the influence of interfering ions and Fe²⁺ oxidation, for example through operational control or the use of freshly prepared FeSO₄ solution to ensure process stability.